2023
DOI: 10.3389/fendo.2022.1065527
|View full text |Cite
|
Sign up to set email alerts
|

Association of bone mineral density with prediabetes risk among African-American and European-American adult offspring of parents with type 2 diabetes

Abstract: IntroductionType 2 diabetes mellitus (T2DM) is associated with alterations in bone mineral density (BMD), but association between prediabetes and BMD is unclear.MethodsWe analyzed BMD among the initially normoglycemic participants in the Pathobiology of Prediabetes in a Biracial Cohort (POP-ABC) study in relation to incident prediabetes during 5 years of follow-up.Results and DiscussionA total of 343 participants (193 Black, 150 White) underwent DEXA during Year 1 of POP-ABC and were followed quarterly for 5 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Fourth, HKOS participants are all Chinese only, the generalizability to other populations is unknown. Nevertheless, similar associations of BMD with prediabetes risk were observed among African‐American and European‐American offspring, [ 28 ] and the MR analysis was conducted using data derived from the European population, both suggesting that such a relationship may also exist in the non‐Chinese population. Fifth, the measurements for glycemic traits and bone turnover markers in HKOS‐B were unavailable and we were unable to examine the prediction of BMD and bone turnover markers on adverse glycemic traits.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Fourth, HKOS participants are all Chinese only, the generalizability to other populations is unknown. Nevertheless, similar associations of BMD with prediabetes risk were observed among African‐American and European‐American offspring, [ 28 ] and the MR analysis was conducted using data derived from the European population, both suggesting that such a relationship may also exist in the non‐Chinese population. Fifth, the measurements for glycemic traits and bone turnover markers in HKOS‐B were unavailable and we were unable to examine the prediction of BMD and bone turnover markers on adverse glycemic traits.…”
Section: Discussionmentioning
confidence: 68%
“…[ 2,27 ] The positive association is in line with a study showing high BMD is associated with higher prediabetic risk and glycemic deterioration. [ 28 ] In the prospective HKOS‐B cohort, we observed that BMD at the femoral neck and total hip but not the lumbar spine was significantly associated with an increased risk of T2DM in the fully adjusted model. This is in agreement with the observation in the cross‐sectional analysis that the association of BMD at the spine with fasting glucose and Hb A1c had a smaller estimate than the BMD at the hip (Table 3).…”
Section: Discussionmentioning
confidence: 96%